Pengaruh Kepemimpinan Transformasional dan Kesejahteraan Organisasi terhadap Kinerja Karyawan melalui Organizational Citizenship Behavior (OCB) sebagai Variabel Intervening pada PT Bank Pembangunan Daerah Sumatera Barat - De Sena, Juliana Angelica; Sari, Marta Widian; Sari, Silvia (Lembaga Yasin AlSys, 2025)
This study aims to analyze the influence of transformational leadership and organizational welfare on employee performance with Organizational Citizenship Behavior (OCB) as an intervening variable at PT Bank Pembangunan Daerah Sumatera Barat. Data collection was conducted through surveys and questionnaires, with a sample of 74 respondents. The analysis method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS). The results of the study indicate that transformational leadership has a positive and significant effect on OCB and employee performance, while organizational welfare has a negative and insignificant effect on OCB, but has a positive and significant effect on employee performance. In addition, OCB does not have a significant effect on employee performance. Testing of intervening variables shows that OCB is unable to mediate the effect of transformational leadership or organizational welfare on employee performance significantly. These findings indicate that inspirational leadership and optimal organizational welfare can improve employee performance, although the role of OCB in this relationship still needs further research.